Antiphospholipid Antibodies and Syndrome - Ricard Cervera (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Antiphospholipid syndrome (APS) is an autoimmune disorder caused by antiphospholipid antibodies. It was characterized by excessive clotting of blood and/or certain complications of pregnancy (premature miscarriages, unexplained fetal death, or premature birth) and the presence of antiphospholipid antibodies (such as anti-cardiolipin antibodies or lupus anticoagulant) in the blood. Fifty percent of people with lupus have APS. The exact pathogenesis of APS is inadequately understood, so no specific treatment is available. This Special Issue of Antibodies focuses on the symptoms, pathogenesis, diagnosis, clinical manifestation, therapy of APS, the new research development of antiphospholipid antibodies, and all the other aspects of APS.